Recent development of endoscopic ultrasonography-guided drainage of pancreatic fluid collections - Dong Kee Jang; Jun Kyu Lee (Society of Gastrointestinal Intervention, 2020)
Peripancreatic fluid collections (PFCs) usually occur as a local complication of acute pancreatitis. In the Atlanta classification revised in 2012, local complications are categorized into acute PFC, acute necrotic collection, pancreatic pseudocyst, and walled-off necrosis. The latter two are indications for drainage. With the development of endoscopic ultrasonography (EUS)-guided interventions, EUS-guided drainage of PFCs is now established as a standard treatment due to the advantages of lower cost, shorter hospital stay, and faster recovery. This article provides a brief introduction of PFCs and information on EUS-guided drainage of PFCs with a review of literature.